ENGLISH-MAJORED STUDENTS’ ATTITUDES TOWARDS PRAGMATIC AWARENESS - Thang, Nguyen Tat (VNU Journal of Foreign Studies; Vol 37 No 1DO - 10.25073/2525-2445/vnufs.4662, 2021)
Good command of language, e.g. vocabulary, grammar, does not always guarantee success in communication. Learners of language need to be equipped with both language and the knowledge of how to use it, i.e. pragmatics. This paper investigates the attitudes of English-majored students at a university in Vietnam towards the knowledge of pragmatics of language learners. Data was collected via a questionnaire and the software SPSS version 20 was used for the analysis. The results showed that the majority of investigated students were aware of the role of pragmatics in their language classes. First year students and fourth year students differed in 3 issues: 1) whether good knowledge of language being enough for communication; 2) willingness to take a course on pragmatics; 3) teachers presenting the knowledge of how to use language officially in classes of language. This indicates that instruction about pragmatic knowledge should be taken into consideration in material design and in language classes.